Pengawasan Aparatur Sipil Negara Sebagai Upaya Preventif Pencegahan Tindak Pidana Korupsi Pada Instansi Bea Cukai - Amar Surya Wicaksana; Fuadi Isnawan (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
Supervision of Civil Servants as a Preventive Measure Against Corruption at Customs Agencies The focus of this study is on the preventive measures implemented by Customs agencies to combat corruption and the challenges faced in these efforts, particularly regarding cases of corruption involving individual employees. This research employs a conceptual approach, a method of legal analysis that assesses whether the applied legal concepts align with their foundational principles. Customs agencies undertake various preventive measures to prevent corruption, including internal control monitoring, employee supervision, gratification control programs, strengthening employee integrity, assistance with facility disclosures, and enforcement of internal compliance. To enhance integrity and prevent corruption violations, Customs collaborates and works with various parties. The obstacles to preventing corruption at Customs are not due to incorrect application or lack of evaluation. Instead, the primary issue lies with individual corruption cases, specifically gratification, which is carried out personally without involvement from other parties or agencies.